Healthcare decision-making capacity in old age: A qualitative study - Amaral, Ana Saraiva; Simões, Mário Rodrigues; Freitas, Sandra; Vilar, Manuela; Sousa, Liliana Baptista; Afonso, Rosa Marina (Frontiers in Psychology, 2022)
Objectives: Research about decision-making capacity has been growing in the last decades. That relates to more concerns regarding patients’ autonomy, and an increase of diseases that can negatively impact capacity. This research aims to: explore perceptions, legal aspects, and assessment procedures related to healthcare decision-making capacity in older adults with cognitive impairment; and study the first version of a new assessment instrument of this capacity. Method: Nine focus groups were conducted, including healthcare, law and justice, nursing home professionals, institutionalized older adults, and dwelling older adults. Focus group discussions followed semi-structured interview scripts, specifically developed for each group. After group discussions, the assessment instrument was presented, and participants were asked to evaluate each item relevance and comprehensibility. Qualitative coding of the transcriptions was performed with resource to MAXQDA, using direct content analysis. Results: Six primary themes emerged from the qualitative analysis: Decision-making capacity features; Abilities implied in decision-making; Factors influencing decision-making; Obstacles to decision-making; Legal aspects; and Assessment procedures. Discussion: Results corroborate previous theoretical formulations of capacity. Generally, research results have implications for clinical and assessment practices, as well as preventive strategies that can improve older adult’s decision-making capacity. Assessment procedures of capacity should include a thorough protocol for the assessment of cognition, functionality, depressive symptoms, and decision-making abilities. In this respect, the need for an assessment tool that can provide valid information during evaluation processes is highlighted. Concerning the strategies to promote decision-making capacity, these rely on improving older adult’s health literacy and healthcare providers communication skills, as well as conduct actions to reduce stigma towards people with dementia.